2015
DOI: 10.3402/ecrj.v2.28947
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of radial EBUS outcome for the diagnosis of peripheral pulmonary lesion: sensitivity and complications

Abstract: BackgroundThe purpose of the current study was to clarify the sensitivity and complication rate of the radial (endobronchial ultrasound, EBUS) without the use of guide-sheath (GS) and fluoroscopy for lung cancer (LC), by measuring the distance from the orifice of the bronchus to the pulmonary lesion, as well as to analyze factors that can predict the diagnostic outcome.Materials and methodsA total of 147 patients with peripheral pulmonary lesions (PPL) underwent radial EBUS-guided transbronchial biopsy (TBB) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…The overall diagnostic yield of radial‐EBUS was 55.9% (95% CI: 44.3–67.9) and the malignant diagnostic sensitivity was 60.8% (95% CI: 46.1–74.2). These figures are consistent with the published literature on radial‐EBUS diagnostic yield which range from 55 to 86%, including a recent large meta‐analysis of 57 studies by Ali et al . reporting a pooled diagnostic yield of 70.5% .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall diagnostic yield of radial‐EBUS was 55.9% (95% CI: 44.3–67.9) and the malignant diagnostic sensitivity was 60.8% (95% CI: 46.1–74.2). These figures are consistent with the published literature on radial‐EBUS diagnostic yield which range from 55 to 86%, including a recent large meta‐analysis of 57 studies by Ali et al . reporting a pooled diagnostic yield of 70.5% .…”
Section: Discussionsupporting
confidence: 91%
“…The overall diagnostic yield of radial-EBUS was 55.9% (95% CI: 44.3-67.9) and the malignant diagnostic sensitivity was 60.8% (95% CI: 46.1-74.2). These figures are consistent with the published literature on radial-EBUS diagnostic yield which range from 55 to 86%, [9][10][11][12][13] including a recent large meta-analysis of 57 studies by Ali et al reporting a pooled diagnostic yield of 70.5%. 3 It is worthwhile noting that some of these studies used additional guidance methods, such as fluoroscopy, curette, virtual bronchoscopy and thin bronchoscope, all of which have the potential of influencing and improving diagnostic yield.…”
Section: Discussionsupporting
confidence: 90%
“…The diagnostic yield with REBUS-GS (72.2%) was comparable to the diagnostic yields reported in other studies (63.9-72.5%) (13)(14)(15)(16). The diagnostic yield for PPLs with REBUS-D by thin bronchoscope (75.9% in total, 78.9% for MT) in the present study was higher than that the diagnostic yields reported in previous studies with therapeutic bronchoscopy (53% in total, 73% for MT) (6,7).…”
Section: Discussionsupporting
confidence: 86%
“…The diagnostic yield has fluctuated from 53% up to 77% [22], which can be increased by ensuring that TBB is performed at the correct location as identified by the EBUS. Tay et al performed a retrospective analysis of 196 consecutive patients who underwent investigation with R-EBUS [23].…”
Section: Discussionmentioning
confidence: 99%